2020
DOI: 10.1177/0363546519897064
|View full text |Cite
|
Sign up to set email alerts
|

Knee Extension Deficit in the Early Postoperative Period Predisposes to Cyclops Syndrome After Anterior Cruciate Ligament Reconstruction: A Risk Factor Analysis in 3633 Patients From the SANTI Study Group Database

Abstract: Background: Cyclops syndrome is characterized by a symptomatic extension deficit attributed to impingement of a cyclops lesion within the intercondylar notch. The syndrome is an important cause of reoperation after anterior cruciate ligament reconstruction (ACLR). It has been suggested that remnant-preserving ACLR techniques may predispose to cyclops syndrome, but there is very limited evidence to support this. In general terms, risk factors for cyclops syndrome are not well-understood. Purpose: To determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 42 publications
(73 reference statements)
1
44
0
3
Order By: Relevance
“…Based on these findings, one might deduce that stump preservation has a protective effect on the development of cyclops lesions. However, a recent study by Delaloye et al, 5 which reported on 3633 patients, found no relationship between reoperation for cyclops lesions and the amount of stump preservation. The authors determined that the most important risk factor for reoperation for a symptomatic cyclops lesion was an extension deficit in the early postoperative period.…”
Section: Discussionmentioning
confidence: 93%
“…Based on these findings, one might deduce that stump preservation has a protective effect on the development of cyclops lesions. However, a recent study by Delaloye et al, 5 which reported on 3633 patients, found no relationship between reoperation for cyclops lesions and the amount of stump preservation. The authors determined that the most important risk factor for reoperation for a symptomatic cyclops lesion was an extension deficit in the early postoperative period.…”
Section: Discussionmentioning
confidence: 93%
“…Pode haver também, uma diminuição da amplitude de movimento, que pode ser resultado do impacto do enxerto e da artrofibrose localizada ou difusa. Essas lesões atléticas são muito comuns, sendo uma das condições mais comumente tratadas do joelho, e podem levar à síndrome do ciclope mesmo após anos da reconstrução (GIACOMO et al 2016;MORRISON, WILLIAM y MAJOR, 2015;BALCAREK et al, 2008;NOAILLES et al, 2019;DELALOYE et al, 2020). Essas consequências podem causar também um tipo de osteoartrite articular (OA), que ocorre quando o tecido flexível nas extremidades dos ossos do joelho se desgasta, isso é particularmente importante, pois lesões anteriores no joelho são um precursor bem reconhecido da OA e existe uma forte possibilidade de que uma incidência crescente de lesões esportivas, que possa resultar em uma carga futura cada vez maior de OA, após a aposentadoria desses atletas (FINCH, KEMP y CLAPPERTON, 2015;BENNELL, HUNTER y VICENZINO, 2012;LOHMANDER et al 2007).…”
Section: Metodologiaunclassified
“…It may be postulated that an ACL injury followed by an ACL reconstruction may aggravate this problem. AKP is also commonly present after ACL reconstruction [8], which might be in uenced by the graft choice, and might lead to persistent knee extensor muscles weakness [8][9][10][11]. It has been proposed that less AKP before the ACL reconstruction is predictive of better clinical outcomes at 12 months post-operative [12,13].…”
Section: Introductionmentioning
confidence: 99%